The Variation in Wage-Ratios - Thorndike, E. L. (Quarterly Journal of Economics, 1940)
Variations in wage-ratios in different areas: conductors and brakemen, 370; typists and stenographers, 370; telephone operators and typists, 370; office work, 370; painters and plumbers, 372; common labor and skilled labor, 373. — Analysis of wage-ratios among railroad workers: engineers, conductors, brakemen, section men, 374. — National differences in these ratios, 375. — Swedish experience, 378. — Engineers and firemen, 378. — American experience, 379. — Length-of-service ratios, 380. — Economic ratios in general, 382.